TINJAUAN HUKUM KEWARISAN ISLAM TERHADAP PENGHAPUSAN BAGIAN ‘ASHABAH AYAH MELALUI PASAL 177 KHI DAN SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 1994 - Nasaiy Aziz (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
There are three ways fathers inherit property, namely the furudl, ashabahand furudl and ashabah. The first inheritance section is said to be received by thefather of 1/6 of the inheritance if the heir leaves the son or grandson of the son ofthe testator. The inheritance section with the ashabah street the father receives theremaining inheritance after being taken by other furudh heirs if the heir does notleave the child altogether, both male and female as well as grandson of the boyand granddaughter of the boys. While the third way, the father receivesinheritance furudh and ashabah in one time if the heir leaves the daughter, becausethe existence of the father can menghijab all heirs other than children andmothers. The addition of furudh for the father, that is 1/3 of the estate and theabolition of the father's ashabah section if the heir does not leave the child orgrandchild of the boy as defined in the KHI article 177 and the Supreme CourtCircular Letter need to be studied further and analyzed from corner of the Law ofInheritance of Islam.